Frailty Assessment Practices Among Members of the Society of Trauma Nurses: An Exploratory Survey - Heather X. Rhodes-Lyons; Gina Brandl; Hilary L.S. Hawkins; Jenna Chatham; Maria Thurston (Journal of Trauma Nursing, 2026)
BACKGROUND: Frailty is an established determinant of adverse outcomes among injured older adults; however, integration into trauma workflows remains variable and national implementation data are limited. OBJECTIVE: To describe frailty screening practices and perceptions among trauma professionals affiliated with the Society of Trauma Nurses. METHODS: This exploratory, descriptive, cross-sectional survey was conducted from November 12, 2025, to January 12, 2026, among trauma professionals at adult US trauma centers. A 14-item, investigator-developed instrument was distributed via electronic mail through the Society of Trauma Nurses membership network. Participation was voluntary and anonymous; survey completion constituted informed consent. Distribution through an open network without a defined sampling frame precluded calculation of a formal response rate. RESULTS: Of 149 surveys initiated, 142 were eligible after excluding 7 responses with missing verification data. Frailty familiarity was reported by 112 of 142 respondents (78.9%); however, only 44 of 142 (31.0%) reported routine use of a standardized screening tool. Frailty scores were used to initiate specialty consultations by 37 of 142 (26.1%) and to inform clinical practice guideline decisions by 25 of 142 (17.6%). Perceived institutional benefit was common: 83 of 142 (58.5%) reported frailty quantification would improve workflow efficiency, and 99 of 142 (69.7%) indicated it would support Trauma Quality Improvement Program geriatric best-practice guideline compliance. CONCLUSIONS: Despite high awareness, standardized frailty screening remains inconsistently implemented across US trauma centers. Findings are hypothesis-generating and underscore the need for structured integration strategies and outcomes-based research.